Multidisciplinary team approach in breast cancer care: Benefits and challenges - Owain Blackwood; Rahul Deb (Wolters Kluwer Medknow Publications, 2020)
The multidisciplinary team approach has been employed internationally for decades, as an attempt to bring collaborative decision-making and concentrate clinical experience from multiple specialties on single patient cases in a systematic fashion. Adoption is not yet worldwide, but is increasing. The role of the histopathologist is central, providing vital information and context to clinical diagnosis and management. Our review summarizes some of the most relevant research on the topic of MDT usage and efficacy in relation to breast cancer, attempting to draw together its advantages and challenges. It is hoped that this review will make a contribution to the current international literature regarding multidisciplinary approaches in breast cancer care.